Faktor-Faktor yang Mempengaruhi Niat Penggunaan Teknologi Berbasis AI dalam Pembelajaran pada Mahasiswa Program Studi Pendidikan Administrasi Perkantoran Universitas Sebelas Maret Surakarta : Penelitian - Khotimah, Siti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aimed to analyze the factors influencing students’ intention to use Artificial Intelligence (AI) based technology in learning activities among students of the Office Administration Education Study Program at Universitas Sebelas Maret. This research employed a quantitative approach by adopting the Technology Acceptance Model (TAM), which included Perceived Ease of Use (PEU), Perceived Usefulness (PU), Behavioral Intention to Use (BI), and Actual Use (AU). The research population consisted of students from the 2021-2024 cohorts, with a total sample of 194 respondents selected using proportionate stratified random sampling. Data were collected through an online questionnaire, while data analysis was conducted using (PLS-SEM) with SmartPLS 3.0 software. The results indicated that PEU had a positive and significant effect on PU and BI AI based technology. Furthermore, PU significantly influenced BI. BI use also had a significant effect on the AU of AI based technology in learning. These findings suggest that perceived ease and usefulness are key factors in encouraging students intention and actual use of AI technology in the learning process